Untapped potential of moving bed biofilm reactors with different biocarrier types for bilge water treatment: A laboratory‐scale study - Mazioti, Aikaterini A; Koutsokeras, Loukas E.; Constantinides, Georgios; Vyrides, Ioannis (My University, 2021)
Two labscale aerobic moving bed biofilm reactor (MBBR) systems, with a different type of biocarrier in each (K3 and Mutag BioChip), were operated in parallel for the treatment of real saline bilge water. During the operation, different stress conditions were applied in order to evaluate the performance of the systems: organic/hydraulic load shock (chemical oxygen demand (COD): 9 g L‐1; hydraulic retention time (HRT): 48–72 h) and salinity shock (salinity: 40 ppt). At the same time, the microbiome in the biofilm and suspended biomass was monitored through 16S rRNA gene analysis in order to describe the changes in the microbial community. The dominant classes were Alphaproteobacteria (families Rhodospirillaceae and Rhodobacteraceae) and Bacteroidia (family Lentimicrobiaceae), being recorded at high relative abundance in all MBBRs. The structure of the biofilm was examined and visualized with scanning electron microscopy (SEM) analysis. Both systems exhibited competent performance, reaching up to 86% removal of COD under high organic loading conditions (COD: 9 g L‐1). In the system in which K3 biocarriers were used, the attached and suspended biomass demonstrated a similar trend regarding the changes observed in the microbial communities. In the bioreactor filled with K3 biocarriers, higher concentration of biomass was ob-served. Biofilm developed on Mutag BioChip biocarriers presented lower biodiversity, while the few species identified in the raw wastewater were not dominant in the bioreactors. Through energy-dispersive X‐ray (EDX) analysis of the biofilm, the presence of calcium carbonate was discovered, indicating that biomineralization occurred.
Keywords: Oily wastewater; Biological treatment; Next-generation sequencing; Biofilm; Bacteria